Prevalence of Port Site Infection in Laparoscopic Surgery in Manipal Teaching Hospital: A Cross-sectional Study - Shrestha, Binod Bade; Mishra, Sushil; Lamsal , Ashbin; Jha , Matsendra (Nepal Journal of Medical Sciences, 2024)
Introduction: Port site infections following laparoscopic surgery, though uncommon, are significant complications. These infections can lead to prolonged hospital stays, increased financial costs, and poor cosmetic outcomes. This study aimed to determine the prevalence of port site infections in laparoscopic surgeries, specifically laparoscopic cholecystectomy, and identify associated factors. Methods: A prospective cross-sectional study was conducted with 538 adult patients, aged 18-86 years, from 01 December 2021 to 31 May 2024, following Institutional Review Board approval (Reference ID: MEMG/485/IRC). Participants who underwent elective laparoscopic cholecystectomy were included via convenience sampling. All the patients received prophylactic antibiotic with injection cefuroxime 1gm at the induction of anesthesia and 1gm iv bd was prescribed for 2 days followed by oral cefixime 200 mg bd for next five days. Variables analysed included port site infections, site of infected port, age, gender, and intraoperative spillage of stones, bile, or pus. Results: The study comprised 538 patients, with 367 females (68.2%) and 171 males (31.8%). The median surgical duration was 30 minutes. Thirteen patients (2.4%) developed port site infections: 12 (2.23%) were under 65 years and one (0.18%) was over 65. Infections occurred in 9 females (1.67%) and 4 males (0.73%). Umbilical port infections (10/1.9%) were more common than epigastric port infections (3/0.6%). Most gallbladder extractions (446/82.9%) were performed through umbilical port. No significant associations were found between port site infections and variables such as age, gender, bile spillage, calculi spillage, and duration of surgery (p value=1.00, 1.00, 0.17, 0.47 and 0.57 respectively). Conclusions: Port site infections after laparoscopic cholecystectomy are infrequent and not significantly influenced by age, gender, bile/calculi spillage, or surgery duration. The preference for umbilical port extraction doesn't significantly affect infection rates. Further research is needed to identify other potential risk factors for these infections.